Hydrogen-reduced stannous tungstate nano material as well as preparation method and application thereof
By heat treatment of stannous tungstate nanomaterial in a hydrogen atmosphere, hydrogen-reduced stannous tungstate nanomaterial was prepared, which solved the problem of insufficient catalytic performance of existing catalysts and significantly improved its photoelectrocatalytic performance and visible light absorption response.
Patent Information
- Application Number
- CN202311316476.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing photoelectric catalytic water decomposition technology, the catalytic performance of the catalyst is insufficient, which affects the industrialization process of the technology.
By heat treatment of the stin tungstate nanomaterial at 500-600°C in an atmosphere containing hydrogen, hydrogen-reduced stin tungstate nanomaterial was prepared to improve its photoelectrocatalytic properties.
This method can significantly improve the photoelectrocatalytic performance of stannous tungstate nanomaterials, make it have stronger absorption response to visible light and have good photocatalytic activity.
Smart Images

Figure CN119797430A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrocatalysis, and in particular relates to a hydrogen-reduced stannous tungstate nanomaterial and a preparation method and application thereof. Background Art
[0002] The efficient use of solar energy is one of the best options to alleviate energy problems. Photoelectrocatalytic water splitting technology can be used to convert solar energy into high-value chemical energy and hydrogen energy. Among them, hydrogen energy has a high combustion value and the combustion products are pollution-free. It is recognized as one of the most promising alternative energy sources to replace fossil fuels in the future. Photoelectrocatalytic water splitting can be carried out at room temperature without focusing sunlight. It can be implemented on a large scale outdoors and in factories with sunlight. At the same time, the photoelectrocatalytic water splitting device can be completely composed of inorganic materials, which is durable, stable and efficient. Photoelectrocatalytic water splitting technology mainly relies on the external voltage generated at the contact interface of semiconductors and electrolyte solutions to promote the separation and redox of photogenerated charges. The intensity of the required external voltage is smaller than that of electrocatalysis, and the energy consumption is lower. Therefore, photoelectrochemical technology has great development potential in obtaining cheap and clean hydrogen energy.
[0003] The catalytic performance of the catalyst is one of the key factors that determine whether the photoelectrocatalytic water splitting technology can be actually industrialized. Therefore, the development of efficient photocatalysts is one of the technical problems that need to be urgently solved in this field. Summary of the invention
[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:
[0005] One of the purposes of the present invention is to provide a method for preparing a hydrogen-reduced stannous tungstate nanomaterial, the preparation method comprising: heat treating the stannous tungstate nanomaterial at a temperature of 500-600° C. in an atmosphere containing hydrogen to obtain the hydrogen-reduced stannous tungstate nanomaterial.
[0006] In the preparation method provided by the present invention, hydrogen can react with the intrinsic oxygen vacancies on the WO4 octahedron with high selectivity compared with other reducing gases, while other reducing gases such as CO and ammonia have weaker reaction activity with it; the effect of heat treatment under the above temperature conditions is good, if the temperature is too high, stannous tungstate will spontaneously undergo phase transformation and thermal decomposition; using the above method to carry out hydrogen reduction treatment on stannous tungstate can improve its photoelectrocatalytic performance.
[0007] In some embodiments, during the heat treatment process, the hydrogen-containing atmosphere is introduced into the heat treatment system at a gas flow rate of 500-800 ml / min. Preferably, the hydrogen-containing atmosphere is introduced into the heat treatment system at a gas flow rate of 600-750 ml / min. An appropriate gas flow rate can ensure that the adsorption and desorption process of the reaction gas on the crystal surface matches the crystal lattice reaction time. Too fast is not conducive to adsorption and desorption, and too slow reaction is incomplete.
[0008] In some embodiments, the heat treatment time is 4-10 hours.
[0009] In some embodiments, the tin tungstate nanomaterial is heated to 500-600° C. at a heating rate of 5-10° C. / min.
[0010] In some embodiments, the atmosphere containing hydrogen is a mixed atmosphere including hydrogen and an inert gas.
[0011] Furthermore, the inert gas includes at least one of argon, nitrogen and helium.
[0012] Furthermore, the mixed atmosphere contains H2 and Ar.
[0013] In some embodiments, the volume concentration of hydrogen in the hydrogen-containing atmosphere is 3-7%.
[0014] In some embodiments, the preparation method of the stannous tungstate nanomaterial includes: subjecting a uniform mixed solution containing a tungsten source and a tin source to a hydrothermal reaction at 180-210° C. to obtain the stannous tungstate nanomaterial.
[0015] In some embodiments, the tungsten source and the tin source are dispersed in an acetic acid / sodium acetate buffer solution with a pH of 3.5-4.2 to obtain the mixed solution.
[0016] In some embodiments, in the mixed solution, the molar ratio of W to Sn in the tungsten source and the tin source is 0.8 to 1.3.
[0017] In some embodiments, in the mixed solution, the concentration of the tungsten source and the tin source is 0.2-0.25 mol / L, that is, the concentration of the tungsten source is 0.2-0.25 mol / L, and / or the concentration of the tin source is 0.2-0.25 mol / L.
[0018] In some embodiments, the tungsten source includes at least one of Na2WO4, K2WO4, CaWO4 and CoWO4.
[0019] In some embodiments, the tin source includes at least one of SnCl2, SnF2, stannous chloride dihydrate and stannous acetate.
[0020] In some embodiments, the reaction time of the hydrothermal reaction is 10-18 hours.
[0021] In some embodiments, the preparation method includes: in a H2 / Ar atmosphere with a hydrogen volume concentration of 5%, heating the stannous tungstate nanomaterial prepared by a hydrothermal method to 500°C for heat treatment, and during the heat treatment process, a gas flow rate of 700 ml / min is introduced into the heat treatment system, and the heat treatment is maintained for 6 hours.
[0022] The second object of the present invention is to provide a hydrogen-reduced stannous tungstate nanomaterial obtained by any of the above-mentioned preparation methods.
[0023] In some embodiments, the particle size of the hydrogen-reduced stannous tungstate nanomaterial is 200-500 nm.
[0024] The third object of the present invention is to provide a method for enhancing the visible light absorption response characteristics of stannous tungstate nanomaterials, comprising: heat treating the stannous tungstate nanomaterials prepared by hydrothermal synthesis in a hydrogen atmosphere, wherein the heat treatment temperature is 500-600°C.
[0025] The specific process conditions of the heat treatment have been described in one of the objectives of the present invention and will not be repeated here.
[0026] A fourth object of the present invention is to provide an application of the hydrogen-reduced stannous tungstate nanomaterial described in any of the above technical solutions in photoelectrocatalytic water decomposition or preparation of photoelectric devices.
[0027] In some embodiments, the application includes: using the hydrogen-reduced stannous tungstate nanomaterial and Co and / or Co-containing materials to perform photoelectrocatalytic water decomposition or prepare photoelectric devices. The inventors found that when the hydrogen-reduced stannous tungstate nanomaterial provided by the present invention is used simultaneously with Co / Co-containing materials, its photoelectric response is significantly improved, indicating that it has a good positive synergistic catalytic effect with Co and / or Co-containing materials.
[0028] A fifth object of the present invention is to provide a method for producing hydrogen by photoelectrocatalytic decomposition of water, comprising:
[0029] A photoelectrochemical reaction system is constructed with an alkaline electrolyte, a cathode and an anode comprising the hydrogen-reduced stannous tungstate nanomaterial described in the above technical solution;
[0030] The photoelectrochemical reaction system is irradiated with visible light, and a voltage is applied between the anode and the cathode to perform photoelectrocatalytic water decomposition to produce hydrogen.
[0031] In some embodiments, the anode further comprises Co and / or a Co-containing material.
[0032] The sixth object of the present invention is to provide a photoanode device, which includes a substrate and a stannous tungstate layer formed on the substrate, and the stannous tungstate layer includes the hydrogen-reduced stannous tungstate nanomaterial described in the above technical solution.
[0033] In some embodiments, the photoanode device further includes a Co catalyst promoter layer, and the Co catalyst promoter layer is stacked adjacent to the stannous tungstate layer.
[0034] In some embodiments, the photoanode device includes a Sn contact layer, a Ni contact layer, the stannous tungstate layer, and the Co promoter layer sequentially formed on the substrate.
[0035] In some embodiments, the Sn contact layer has a thickness of 3.5-5 um.
[0036] In some embodiments, the Ni contact layer has a thickness of 80 nm to 150 nm.
[0037] In some embodiments, the thickness of the stannous tungstate layer is 200-500 nm.
[0038] In some embodiments, the thickness of the Co promoter layer is 4-10 nm.
[0039] The preparation method of the photoanode device comprises: coating the hydrogen-reduced stannous tungstate nanomaterial on a first substrate, forming the stannous tungstate layer after drying, and sequentially vapor-depositing a Ni contact layer and a Sn contact layer on the stannous tungstate layer to form a stannous tungstate layer / Ni contact layer / Sn contact layer; peeling the stannous tungstate layer / Ni contact layer / Sn contact layer from the first substrate and adhering them to a second substrate, and adhering the Sn contact layer to the second substrate in a manner that the Sn contact layer is adjacent to the second substrate; and then vapor-depositing a Co catalyst layer on the stannous tungstate layer to obtain the photoanode device.
[0040] The seventh object of the present invention is to provide a method for photoelectrocatalytic decomposition of water to produce hydrogen, the method comprising: using an alkaline aqueous solution containing 0.1-0.8 mol / L Na2SO3, methanol, triethylamine and 10-40% hydrogen peroxide as an electrolyte, using the photoanode device described in any of the above technical solutions as a working electrode, using a platinum electrode as a counter electrode and Ag / AgCl as a reference electrode, and performing photoelectrocatalytic decomposition of water under illumination and with / without an external bias.
[0041] In some embodiments, the light intensity is 40 mW / cm 2 ~100mW / cm 2 (AM 1.5G).
[0042] In some embodiments, the external bias voltage is 0-1.23 V vs RHE.
[0043] Compared with the prior art, the present invention has at least the following beneficial effects: the present invention utilizes the reducing property of hydrogen to regulate the formation of oxygen vacancies in stannous tungstate crystals, promotes the rearrangement of crystals, and has the characteristics of uniform morphology and fewer defects in the crystals compared with stannous tungstate synthesized by general heat treatment or hydrothermal method; in the energy band structure of the hydrogen-reduced stannous tungstate nanomaterial provided by the present invention, the defect energy level of the oxygen vacancies induced by hydrogen is more downwardly shifted compared with the defect energy level generated by the hydrothermal method and general heat treatment (such as inert atmosphere heat treatment) of the material, which reduces the conduction band edge of the material, reduces the band gap width of the material, and enhances its absorption response to visible light, so it has good photocatalytic activity. Under the same illumination test conditions, the photoelectric performance of the stannous tungstate nanomaterial treated by hydrogen reduction is about one order of magnitude higher than that of the stannous tungstate nanomaterial treated by inert atmosphere and not treated by heat. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 This is a SEM image of the hydrogen-reduced stannous tungstate nanomaterial prepared in Example 1 of the present invention;
[0046] Figure 2 is a SEM image of the stannous tungstate nanomaterial subjected to heat treatment in an inert atmosphere (argon) in Comparative Example 6;
[0047] Figure 3 This is the SEM image of the tin tungstate nanomaterial prepared by hydrothermal method without heat treatment in Example 5.
[0048] Figure 4 It is the XPS graph of element O of the stannous tungstate nanomaterial prepared by the hydrothermal method (Comparative Example 5), inert atmosphere (Comparative Example 6) and hydrogen reduction (Example 1);
[0049] Figure 5 It is the XPS graph of the element Sn of the stannous tungstate nanomaterial prepared under the hydrothermal method (Comparative Example 5), inert atmosphere (Comparative Example 6) and hydrogen reduction (Example 1);
[0050] Figure 6It is the XRD pattern of the stannous tungstate nanomaterial prepared under air, inert atmosphere (Comparative Example 6) and hydrogen reduction (Example 1);
[0051] Figure 7 is an appearance diagram of the photoanode device prepared in Example 1 of the present invention;
[0052] Figure 8 is a surface morphology SEM image of the photoanode device prepared in Example 1 of the present invention;
[0053] Fig. 9 The photoanode device prepared in Example 1 of the present invention is in a 0.2M Na2SO3 pH=9 boric acid buffer solution, 100mW / cm 2 , Cyclic voltammetry curve under 455nm illumination;
[0054] Fig.10 The photoanode device prepared in Example 1 and Comparative Example 1 was 40 mW / cm in a boric acid buffer at room temperature and pH = 9. 2 Comparison of cyclic voltammetry curves under AM 1.5G illumination conditions;
[0055] Fig.11 The photoanode device prepared in Examples 7 to 11 was placed in a 0.2M Na2SO3 pH=9 boric acid buffer solution at 100 mW / cm 2 , Cyclic voltammogram under 455nm illumination;
[0056] Fig.12 The photoanode device prepared in Examples 12 to 15 was placed in a 0.2M Na2SO3 pH=9 boric acid buffer solution at 100 mW / cm 2 , Cyclic voltammogram under 455nm illumination;
[0057] Fig.13 The photoanode devices in Examples 1, 4, 5, 6 and Comparative Examples 2 to 4 were in a 0.2M Na2SO3 pH=9 boric acid buffer solution at 100 mW / cm 2 , cyclic voltammogram under 455nm illumination conditions. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0059] Example 1
[0060] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0061] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 700ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0062] The SEM and XRD patterns of the hydrogen-reduced tin tungstate nanomaterials prepared in this example are shown in Figures 1 and 2. Figure 1 , Figure 6 shown.
[0063] The steps of preparing a photoanode device using the above hydrogen-reduced stannous tungstate nanomaterial are as follows:
[0064] The hydrogen-reduced stannous tungstate nanomaterial powder is dispersed in isopropanol (the mass ratio of powder to isopropanol is 1:20-40), and ultrasonicated for 30 minutes; the solution is evenly dripped on a clean glass substrate, and after it is naturally dried, the dripping is repeated 4-6 times to form a hydrogen-reduced stannous tungstate coating;
[0065] Then, the glass substrate with stannous tungstate coating was placed in a thermal evaporation vacuum coating machine, and high-purity metal (99.99%) Ni and Sn were used as evaporation sources. Under vacuum conditions, a Ni contact layer of 100nm and a Sn contact layer of 4um were sequentially deposited to obtain a stannous tungstate layer / Ni contact layer / Sn contact layer structure.
[0066] Then, the stannous tungstate layer / Ni contact layer / Sn contact layer was peeled off on the Sn contact layer with adhesive tape and adhered to a new clean glass substrate. The glass substrate was placed in deionized water for ultrasonic treatment for 5 min, taken out and dried;
[0067] The glass substrate after ultrasonication was placed in a thermal evaporation vacuum coating machine, and high-purity metal (99.99%) Co was used as the evaporation source. Under vacuum conditions, a 4nm Co catalyst layer was thermally evaporated to obtain a structure of Co catalyst layer / stannous tungstate layer / Ni contact layer / Sn contact layer / glass substrate; finally, the edges of the substrate were encapsulated with epoxy resin to obtain a photoanode device. Figure 7 This is the appearance diagram of the device obtained in this embodiment. Figure 8 SEM image of the microstructure of the prepared device.
[0068] The photoelectrocatalytic performance of the above-mentioned photoanode device was tested as follows:
[0069] The three-electrode system was used for the test, with the above-mentioned photoanode device as the working electrode, platinum wire as the counter electrode, Ag / AgCl as the reference electrode, the electrolyte containing 0.2 mol / L Na2SO3, pH = 9 boric acid buffer (0.5 mol / L), and the light intensity of 100 mW / cm at a wavelength of 455 nm. 2 Monochromatic light, linear voltammetry test scan rate is 5mV / s, the test results are as follows Fig. 9 As shown, the photocurrent density can reach up to 1.1 mA / cm near 1 V (V vs RHE). 2 , indicating that the photoanode device prepared in this embodiment has a higher photoelectric response.
[0070] Example 2
[0071] 1.14g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0072] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 700ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0073] Example 3
[0074] 0.76g SnCl2 and 1.18g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed with deionized water for several times, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0075] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 700ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0076] Example 4
[0077] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0078] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0079] The hydrogen-reduced stannous tungstate nanomaterial prepared in this example was used to prepare a photoanode device in the same manner as in Example 1, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0080] Example 5
[0081] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0082] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 800ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0083] The hydrogen-reduced stannous tungstate nanomaterial prepared in this example was used to prepare a photoanode device in the same manner as in Example 1, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0084] Example 6
[0085] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0086] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 600ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0087] The hydrogen-reduced stannous tungstate nanomaterial prepared in this example was used to prepare a photoanode device in the same manner as in Example 1, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0088] Example 7
[0089] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0090] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 500°C, maintained for 4 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0091] The steps of preparing a photoanode device using the above hydrogen-reduced stannous tungstate nanomaterial are as follows:
[0092] The hydrogen-reduced stannous tungstate nanomaterial powder is dispersed in isopropanol (the mass ratio of powder to isopropanol is 1:20-40), and ultrasonicated for 30 minutes; the solution is evenly dripped on a clean glass substrate, and after it is naturally dried, the dripping is repeated 4-6 times to form a hydrogen-reduced stannous tungstate coating;
[0093] Then, the glass substrate with stannous tungstate coating was placed in a thermal evaporation vacuum coating machine, and high-purity metal (99.99%) Ni and Sn were used as evaporation sources. Under vacuum conditions, a Ni contact layer of 100nm and a Sn contact layer of 4um were sequentially deposited to obtain a stannous tungstate layer / Ni contact layer / Sn contact layer structure.
[0094] Then, use tape to peel off the stannous tungstate layer / Ni contact layer / Sn contact layer on the Sn contact layer and stick it to a new clean glass substrate. Place the glass substrate in deionized water for 5 minutes of ultrasound, take it out and dry it; finally, use epoxy resin to encapsulate the edges of the substrate to obtain a photoanode device.
[0095] The photoanode device of this embodiment was used as the working electrode, and a three-electrode system was assembled in the same manner as in Example 1, and a photoelectrocatalytic water decomposition activity test was performed. The test results are shown in Table 1.
[0096] Example 8
[0097] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0098] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 500°C, maintained for 6 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0099] The hydrogen-reduced stannous tungstate nanomaterials prepared in this example were used to prepare photoanode devices in the same manner as in Example 7, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0100] Example 9
[0101] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0102] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 500°C, maintained for 10 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0103] The hydrogen-reduced stannous tungstate nanomaterials prepared in this example were used to prepare photoanode devices in the same manner as in Example 7, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0104] Example 10
[0105] The only difference between Example 10 and Example 7 is that the temperature is raised to 500° C. and maintained for 2 hours. The rest is the same as Example 7.
[0106] Embodiment 11
[0107] The only difference between Example 11 and Example 7 is that the temperature is raised to 500° C. and maintained for 8 hours. The rest is the same as Example 7.
[0108] Example 12
[0109] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0110] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 550°C, maintained for 2h, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0111] The hydrogen-reduced stannous tungstate nanomaterials prepared in this example were used to prepare photoanode devices in the same manner as in Example 7, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0112] Example 13
[0113] 0.95g SnCl2 and 1.47g Na2WO4 were dissolved in acetic acid / sodium acetate buffer solution of pH=4 to obtain 20ml SnCl2 solution and 20ml Na2WO4 solution, which were magnetically stirred for 5 minutes respectively; then the SnCl2 solution was added dropwise to the Na2WO4 solution, and stirred vigorously for 10 minutes after completion; then the mixed solution was transferred to a 50ml hydrothermal kettle, sealed and placed in a 200℃ oven for reaction for 12 hours, and taken out after natural cooling; it was centrifuged and washed several times with deionized water, and the precipitate was dried in a constant temperature vacuum drying oven at 60℃ for 12 hours to obtain stannous tungstate nanomaterial.
[0114] The powder of the stannous tungstate nanomaterial obtained above was ground for 10 minutes and then placed in a closed tubular furnace. The tube was evacuated and filled with 5% H2 / Ar mixed gas, and the evacuation and filling were repeated for more than 3 times. The heating rate was set at 10°C / min, the gas flow rate of the 5% H2 / Ar mixed gas was 500ml / min, the temperature was raised to 550°C, maintained for 4 hours, and then allowed to cool naturally to obtain hydrogen-reduced stannous tungstate nanomaterial.
[0115] The hydrogen-reduced stannous tungstate nanomaterials prepared in this example were used to prepare photoanode devices in the same manner as in Example 7, and assembled into a three-electrode system for photoelectrocatalytic water decomposition activity testing. The test results are shown in Table 1.
[0116] Embodiment 14
[0117] The only difference between Example 14 and Example 12 is that the temperature is raised to 550° C. and maintained for 6 hours. The rest is the same as Example 12.
[0118] Embodiment 15
[0119] The only difference between Example 15 and Example 11 is that the temperature is raised to 550° C. and maintained for 8 hours. The rest is the same as Example 12.
[0120] Comparative Example 1
[0121] The difference between Comparative Example 1 and Example 1 is that the photoanode device is directly prepared using the stannous tungstate nanomaterial prepared by the hydrothermal method without hydrogen reduction. The other steps are the same as those in Example 1 to obtain the photoanode device.
[0122] Fig.10 The photoanode device prepared in Example 1 and Comparative Example 1 was 40 mW / cm in a boric acid buffer at room temperature and pH = 9. 2 Comparison of cyclic voltammetry curves under AM 1.5G illumination conditions, from Fig.10 It can be seen that the device based on stannous tungstate reduced by hydrogen has a better photoelectric response.
[0123] Comparative Example 2
[0124] The difference between Comparative Example 2 and Example 1 is that, during the preparation of hydrogen reduction of stannous tungstate, the gas flow rate is 200 ml / min.
[0125] Comparative Example 3
[0126] The difference between Comparative Example 3 and Example 1 is that, during the preparation of hydrogen reduction of stannous tungstate, the gas flow rate is 300 ml / min.
[0127] Comparative Example 4
[0128] The difference between Comparative Example 4 and Example 1 is that, during the preparation of hydrogen reduction of stannous tungstate, the gas flow rate is 400 ml / min.
[0129] Comparative Example 5
[0130] The same hydrothermal method as in Example 1 was used to prepare the stannous tungstate nanomaterial, without hydrogen thermal reduction treatment. The SEM image of the obtained stannous tungstate nanomaterial is as follows: Figure 3 The XPS graphs of O and Sn are shown as follows: Figure 4 , 5 shown.
[0131] Comparative Example 6
[0132] The difference between this comparative example and Example 1 is that the 5% H2 / Ar mixed gas is replaced by pure argon gas, and the other steps are the same as Example 1 to obtain a tin tungstate nanomaterial heat-treated with an inert gas. The SEM of the nanomaterial is as follows: Figure 2 The XPS graphs of O and Sn are shown as follows: Figure 4 , 5 Its XRD pattern is shown in Figure 6 shown.
[0133] Comparative Example 7
[0134] The difference between this comparative example and Example 1 is that the 5% H2 / Ar mixed gas is replaced by air, and the other steps are the same as Example 1 to obtain an air-heat-treated tin tungstate nanomaterial, whose XRD pattern is as follows: Figure 6 shown.
[0135] The cyclic voltammograms of the photoanode devices prepared in Examples 7 to 11 are as follows: Fig.11 The cyclic voltammograms of the photoanode devices prepared in Examples 12 to 15 are shown in Fig.12As shown; Examples 1, 4, 5, 6, Comparative Examples 2 to 4 of the photoanode device cyclic voltammogram as shown Fig.13 shown.
[0136] The photoanode devices of Examples 1, 4-15, and Comparative Examples 2-3 were subjected to a 100 mW / cm 2 The performance test was carried out under 455nm light conditions, and the results are shown in Table 1.
[0137] Table 1 Photoelectrocatalytic water splitting activity of photoanode devices of Examples and Comparative Examples
[0138]
[0139]
[0140] In addition, the photoelectrocatalytic water splitting activity of the photoanode devices of Example 1 and Comparative Example 1 was tested at room temperature in a boric acid buffer solution with a pH of 9 and an illumination condition of 40 mW / cm2 AM 1.5G. The test results are shown in Table 2.
[0141] Table 2 Photoelectrocatalytic water splitting activity of the photoanode devices of Example 1 and Comparative Example 1 under simulated sunlight conditions
[0142]
[0143] It can be seen from Tables 1 and 2 that the hydrogen-reduced stannous tungstate nanomaterials and photoanode devices that conform to the technical solution of the present invention show relatively good photoelectric response in the application of photoelectrocatalytic water electrolysis.
[0144] Combining the comparative examples 4 and 8, it can be seen that under the same other process conditions, the photoanode device loaded with the Co co-catalyst layer exhibits better photoelectrocatalytic water decomposition activity, indicating that there is a good synergistic catalytic effect between the hydrogen reduction of stannous tungstate nanomaterials and Co in the present invention.
[0145] In summary, the hydrogen reduction treatment method provided by the present invention can make the stannous tungstate nanomaterial have a lower overpotential and a higher carrier concentration, so that its response to visible light is improved, and it can be used as a photoanode material in the field of photoelectrocatalytic water decomposition; the stannous tungstate material synthesized by ordinary hydrothermal method can achieve the same order of magnitude as the performance of the stannous tungstate film produced by magnetron sputtering and physical / chemical vapor deposition after hydrogen reduction heat treatment, and the present invention has lower cost than magnetron sputtering, physical / chemical vapor deposition and other methods, simpler process, and higher large-scale production and industrial application value.
[0146] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0147] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0148] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A method for preparing a hydrogen-reduced stannous tungstate nanomaterial, characterized in that: include: In an atmosphere containing hydrogen, the stannous tungstate nanomaterial is heat-treated at a temperature of 500-600° C. to obtain the hydrogen-reduced stannous tungstate nanomaterial.
2. The preparation method according to claim 1, characterized in that: Specifically include: During the heat treatment process, the hydrogen-containing atmosphere is introduced into the heat treatment system at a gas flow rate of 500-800 ml / min, preferably at a gas flow rate of 600-750 ml / min; And / or, the heat treatment time is 4-10h; and / or, heating the stannous tungstate nanomaterial to 500-600° C. at a heating rate of 5-10° C. / min; And / or, the atmosphere containing hydrogen is a mixed atmosphere comprising hydrogen and an inert gas; preferably, the inert gas comprises at least one of argon, nitrogen and helium; And / or, in the hydrogen-containing atmosphere, the volume concentration of hydrogen is 3-7%.
3. The preparation method according to claim 1, characterized in that: The preparation method of the stannous tungstate nanomaterial comprises: subjecting a uniform mixed solution containing a tungsten source and a tin source to a hydrothermal reaction at a temperature of 180-210° C. to obtain the stannous tungstate nanomaterial.
4. The preparation method according to claim 3, characterized in that: Specifically include: Dispersing a tungsten source and a tin source in an acetic acid / sodium acetate buffer solution with a pH of 3.5-4.2 to obtain the mixed solution; and / or, in the mixed solution, the molar ratio of W to Sn in the tungsten source and the tin source is 0.8 to 1.3; And / or, in the mixed solution, the concentration of the tungsten source and the tin source is 0.2-0.25 mol / L; and / or, the tungsten source comprises at least one of Na2WO4, K2WO4, CaWO4 and CoWO4; and / or, the tin source comprises at least one of SnCl2, SnF2, stannous chloride dihydrate and stannous acetate; And / or, the reaction time of the hydrothermal reaction is 10-18h.
5. The hydrogen-reduced stannous tungstate nanomaterial obtained according to the preparation method according to any one of claims 1 to 4.
6. A method for enhancing the visible light absorption response characteristics of stannous tungstate nanomaterials, characterized in that: include: The stannous tungstate nanomaterial prepared by a hydrothermal synthesis method is heat-treated in a hydrogen atmosphere, wherein the heat-treatment temperature is 500-600°C.
7. Use of the hydrogen-reduced stannous tungstate nanomaterial according to claim 5 in photoelectrocatalytic water decomposition or preparation of photoelectric devices; preferably, the application includes: The hydrogen-reduced stannous tungstate nanomaterial is used with Co and / or Co-containing materials to perform photoelectrocatalytic water decomposition or prepare a photoelectric device.
8. A method for producing hydrogen by photoelectrocatalytic decomposition of water, characterized in that: include: A photoelectrochemical reaction system is constructed with an alkaline electrolyte, a cathode, and an anode comprising the stannous tungstate nanomaterial for hydrogen reduction according to claim 5; Irradiating the photoelectrochemical reaction system with visible light and applying a voltage between the anode and the cathode to perform photoelectrocatalytic water decomposition to produce hydrogen; Preferably, the anode further comprises Co and / or a Co-containing material.
9. A photoanode device, characterized in that: It comprises a substrate and a stannous tungstate layer formed on the substrate, wherein the stannous tungstate layer comprises the hydrogen-reduced stannous tungstate nanomaterial as claimed in claim 5; Preferably, the photoanode device further comprises a Co catalyst promoter layer, and the Co catalyst promoter layer is stacked adjacent to the stannous tungstate layer; More preferably, the photoanode device comprises a Sn contact layer, a Ni contact layer, the stannous tungstate layer and the Co co-catalyst layer which are sequentially formed on the substrate.
10. A method for producing hydrogen by photoelectrocatalytic decomposition of water, characterized in that: include: An alkaline aqueous solution containing 0.1-0.8 mol / L Na2SO3, methanol, triethylamine and 10-40% hydrogen peroxide is used as an electrolyte, the photoanode device described in claim 9 is used as a working electrode, a platinum electrode is used as a counter electrode, and Ag / AgCl is used as a reference electrode, and photoelectrocatalytic water decomposition is carried out under light and with or without bias.